Forecasting The Number of Health Center Patient Arrivals Using Cheng’s Fuzzy Time Series Method - Aisyah, Aisyah; Rakhmawati, Fibri (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
Forecasting is the science and art of estimating future events. Forecasting is useful in predicting events covering the short, medium and long term. In the historical data that will be taken and project it into the future so that it involves a forecast, the forecasting involvement uses the amount of data that has been taken. The number of patient arrivals at the health center has increased and decreased every month, this increase and decrease can affect the facilities provided by the health center, so this study intends to do forecasting on the number of health center patient arrivals to meet the service facilities that must be provided. This study was carried out from January 2022 to December 2023 at the Medan Amplas Health center by utilizing Cheng's Fuzzy Times Series method, therefore the results of this calculation were 70,464 patients by getting a MAPE value of 8%.